FISHERY RESOURCES AND ECOLOGY OF TOBA LAKE - Wijopriono Wijopriono; Kunto Purnomo; Endi Setiadi Kartamihardja; Zulkarnaen Fahmi (Indonesian Fisheries Research Journal, 2010)
Investigatiorr of stock and distribution of fishery resources was done in Toba Lake in October 2005, at the time when the wet season prevailed, using acoustic method. Split-beam echosounder SIMRAD Ey-60 operated at frequency ol iZO KHz and 0.512 ms pulse duration was used.